Caring Ability of Postcaesarean Mothers and Itâs Association with Cultural Value - Hodikoh, Atik; Setyowati, Setyowati (Jurnal NERS, 2015)
Introduction: Ability to care of postcaesarean mother affected by multifactor; moternal characteristic, knowledge and cultural values. Postcaesarean mother has high level of dependency in performing selfcare and baby care. The aim of this study was to identified of selfcare and baby care and relation with that factors and cultural behaviour associaated pospartum care. Method: this study used cross sectional design with a purpossive sampling of 66 post caesarean mother ini five hospital in West Java. Instrumen used consisted of maternal characteristic including ages, parity,job, income, knowledga, cultural values, cultural behaviour and observasional instruments of the ability to care. Result: there was a significant relationship between job characteristic and cultural values with the ability to care, for the correlation r 0.295 an 0.355 (p value = 0.003). Discussion: nurses must perform a cultural approach in facilitating the mother to care for themselves and care for the baby in accordance with their cultural values, so that the mother can perform optimally care. Keywords: ability to, cultural values, job, postcaesarean care